Efectos de la facilitación neuromuscular propioceptiva sobre la fuerza muscular en pacientes con lesión del ligamento colateral interno de rodilla del Hospital Básico 11 BCB Galápagos2018 - Marín Parra, Lupe Enriqueta (2018)
The research entitled "Effects of Proprioceptive Neuromuscular Facilitation on Muscle Strength in Patients with Injury to the Internal Collateral Ligament of the Basic Hospital 11 BCB Galápagos", aimed to determine the effect of the Proprioceptive Neuromuscular Facilitation (FNP) exercises on the muscular strength. The approach of the technique is to reach the highest level of functionality of the patient thus achieving motor control and learning, integrating: nerves, muscles and sensory receptors. The design of the investigation is field since it was made data collection in the place of the facts. Of a prospective nature recording the information as the phenomena are occurring. Deductive for the organization of the theoretical bases of diagnosis and the state of the art. The type is quantitative, it uses the data collection based on the numerical valuation and the statistical analysis that allows to establish conclusions of the investigative work. In addition to documentary type since the research is based on scientific and longitudinal evidence because a period of time is established. The level is descriptive taking into account the characteristics of each patient according to the state of the injury. Of applicative character, the proprioceptive neuromuscular facilitation technique was used in the approach of the patient with injury of the internal collateral knee ligament. The technique used was observation by taking information and recording it for later analysis, evidencing the evolution of the patient. The instrument is the clinical history of the Ministry of Public Health, which was modified according to the needs of the research work. The tests used were: analog pain scale, goniometric test and Daniels test. The data was processed by descriptive statistics supported by the SPSS software. The population in which the technique was applied was twenty patients. The results obtained in the investigation showed that the gender with the highest incidence of internal collateral knee ligament injury (LCI) is male, with a percentage of 100%. The duration of the research project was two months, reducing the pain from 7/10 to 0/10, expanding the range of motion in knee flexion from 110 ° to 135 ° and increasing muscle strength from grade 2 to grade 5. Data that were compared with similar research in which it is consistent with the criterion of the reference authors, who indicate that FNP is an effective technique since it increases joint flexibility, reduces pain and increases muscle strength.